Clinical Pharmacogenetics Implementation Consortium (CPIC) Guideline for the Use of Potent Volatile Anesthetic Agents and Succinylcholine in the Context of RYR1 or CACNA1S Genotypes. Issue 6 (24th January 2019) - Gonsalves, Stephen G.; Dirksen, Robert T.; Sangkuhl, Katrin; Pulk, Rebecca; Alvarellos, Maria; Vo, Teresa; Hikino, Keiko; Roden, Dan; Klein, Teri E.; Poler, S. Mark; Patel, Sephalie; Caudle, Kelly E.; et al.
Abstract : The identification in a patient of 1 of the 50 variants in the RYR1 or CACNA1S genes reviewed here should lead to a presumption of malignant hyperthermia susceptibility (MHS). MHS can lead to life‐threatening reactions to potent volatile anesthetic agents or succinylcholine. We summarize evidence from the literature supporting this association and provide therapeutic recommendations for the use of these agents in patients with these RYR1 or CACNA1S variants (updates athttps://cpicpgx.org/guidelines andwww.pharmgkb.org ).